2010
DOI: 10.1177/112070001002000404
|View full text |Cite
|
Sign up to set email alerts
|

The use of a Constrained Cementless Acetabular Component for Instability in Total Hip Replacement

Abstract: Recurrent dislocation after total hip arthroplasty is a disabling complication that can be difficult to treat. We evaluated the early clinical and radiographic outcome associated with the use of a constrained acetabular component for instability in total hip arthroplasty. Fifteen patients underwent either primary or revision total hip arthroplasty with a cementless constrained acetabular component for different indications. The mean patient age at surgery was 57.4 years and the mean clinical and radiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Callaghan et al [25] reported a series of 31 hips with constrained liners implanted into well-fixed acetabular components, and found that 94% of patients were failure-free at an average follow up of nearly 4 years. Significant improvements in dislocation rates with the use of constrained liners in previously unstable THAs were also noted in more recent series [80,81] . Constrained liners offer a valuable option for the management of recurrent dislocations when no obvious cause for dislocation can be identified or if the dislocation is due to soft-tissue deficit that is not otherwise repairable.…”
Section: Constrained Linersmentioning
confidence: 79%
See 1 more Smart Citation
“…Callaghan et al [25] reported a series of 31 hips with constrained liners implanted into well-fixed acetabular components, and found that 94% of patients were failure-free at an average follow up of nearly 4 years. Significant improvements in dislocation rates with the use of constrained liners in previously unstable THAs were also noted in more recent series [80,81] . Constrained liners offer a valuable option for the management of recurrent dislocations when no obvious cause for dislocation can be identified or if the dislocation is due to soft-tissue deficit that is not otherwise repairable.…”
Section: Constrained Linersmentioning
confidence: 79%
“…This device is particularly useful for the surgical management of recurrent dislocation in the setting of abductor deficiency, recurrent dislocation of undetermined etiology and in patients with multiple dislocations due to neurological impairment [16] . The success of constrained liners for instability in these specific situations has been well-documented in the literature [4,5,12,[78][79][80][81] . Additionally, constrained liners offer the ability provide enhanced stability to a hip without the need to revise well-fixed, well-positioned acetabular components [16] .…”
Section: Constrained Linersmentioning
confidence: 99%
“…Constrained liners are for patients with well-positioned implants and patient-related factor for instability or in cases with an incompetent abduction mechanism; these implants should only be used in salvage procedures in elderly and/or low-demand patients with hip instability (9496). There have also been case reports of the mechanical failure of these devises (97).…”
Section: Treatment Options For Dislocation Following Thamentioning
confidence: 99%
“…Published data is currently only available for a few of the constrained liners: Osteonics and Omnifit (Osteonics Corp./Stryker Howmedica) [921], Trident (Stryker) [22, 23], S-ROM (DePuy) [2426], Duraloc (DePuy) [27, 28], Ringloc (Biomet) [20, 29], and Trilogy (Zimmer) [20, 28, 29]. Some of the studies include patients with more than one brand of liner [20, 24, 25, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…We inserted constrained liners as a measure to prevent further dislocations in patients with repeated dislocations, and the constrained liner has not been used in primary surgery in the present series. Some of the published papers deal with a similar material [13, 14, 17, 22, 29], the rest of the published data are on a more diverse group of patients with indications varying from repeated dislocations or intraoperative instability (both primary procedures and revisions) to neurologic impairment and revision procedures on patients with Girdlestone status [911, 15, 16, 1821, 2325, 27, 28]. …”
Section: Discussionmentioning
confidence: 99%